Youth With Chronic Pain and a History of Adverse Childhood Experiences in the Context of Multidisciplinary Pain Rehabilitation. Issue 5 (May 2019) - Nelson, Sarah; Smith, Kelly; Sethna, Navil; Logan, Deirdre
Abstract : Objectives: Previous research has shown that youth with chronic pain who presented for a multidisciplinary evaluation report a history of adverse childhood experiences (ACEs) (eg, abuse, neglect, parent/guardian separation or divorce) at a high rate (over 80%) and that those with pain and ACEs experience increased psychosocial impairment. Outside of chronic pain, evidence also suggests that youth with a history of ACEs experience poorer treatment outcomes. However, no study to date has examined treatment outcomes in youth with chronic pain and a history of ACEs. The current study aimed to examine the role of ACEs in multidisciplinary intensive pain rehabilitation treatment outcomes for youth with chronic pain. Methods: The sample included 305 youth who had undergone intensive pain rehabilitation. Outcomes examined included pain-related and psychosocial impairment measured at baseline and discharge from the program. Results: Results indicated that ∼59% of this sample reported a history of ACEs with ∼21% reporting a history of ≥2 ACEs. At baseline, youth with an ACEs history reported higher somatic symptoms. However, no significant interaction was found across treatment timepoints between ACEs history and time. Conclusions: ACEs history was not a significant factor in treatment outcomes for youth with chronic pain who presented to intensive pain rehabilitation. However, the difference in report of ACEs history across treatment settings indicates that ACEs may be a barrier for youth to engage in recommended outpatient treatment before presenting to pain rehabilitation. Research is needed to further examine this phenomenon.